Methylenetetrahydrofolate reductase polymorphisms as risk factors for retinal venous occlusive disease: A literature review. Issue 3 (May 2021) - Marques, Manuel; Alves, Francisco; Leitão, Miguel; Rodrigues, Catarina; Ferreira, Joana Tavares
The role of polymorphisms of methylenetetrahydrofolate reductase (MTHFR) gene in retinal vein occlusion (RVO) is a theme of discussion since the first reports of RVO in patients with MTHFR C677T mutation and without classic acquired risk factors for retinal vascular disease. The association between MTHFR polymorphisms and RVO has been studied over the last 20 years producing conflicting results. This review aims to summarize the literature concerning the role MTHFR polymorphisms as risk factors for RVO.